Factors influencing treatment decisions in HIFU treatment of adenomyosis: A retrospective study - Zhong, Qiao; Yang, Mei-Jie; Hu, Yan; Jiang, Li; Yu, Jing-Wen; Chen, Jin-Yun; Chen, Wen-Zhi (Frontiers in Surgery, 2022)
Objective: To explore the influencing factors of decision-making in patients with adenomyosis, who are receiving high-intensity focused ultrasound (HIFU) treatment. Methods: A total of 776 patients with adenomyosis were enrolled into HIFU group (241 cases) and hysterectomy group (535 cases) according to the treatment methods. The general data, clinical symptoms, marital and childbearing history, and economic status were compared between the two groups, and factors with P<0.05 were introduced into multivariate logistic regression analysis to determine the determinants of patients choosing HIFU. Results: The average age of the patients in the HIFU group was 39.1±5.2 years, which was lower than that in the hysterectomy group, which was 45.1±3.9 years (P<0.05). The basic medical insurance for urban workers in the HIFU group was more than the hysterectomy group (P<0.05). 95.9% of the hysterectomy group had no desire to have children, compared to 60.6% of the HIFU group, the difference was significant (P<0.05). The treatment costs of HIFU group were significantly lower than that of hysterectomy group (P<0.05). The main symptoms of the two groups were dysmenorrhea, menorrhagia, and secondary anemia. The results of multivariate logistic regression analysis showed that 31-40 years old, fertility desire, dysmenorrhea, menorrhagia, anemia and dizziness and fatigue were the influencing factors for the decision-making of HIFU for patients with adenomyosis. Conclusion: 31-40 years old, fertility desire, dysmenorrhea, menorrhagia, anemia and dizziness and fatigue were the influencing factors for patients to choose HIFU treatment. HIFU therapy has emerged as a new option for patients with adenomyosis as an alternative to hysterectomy.